PENGARUH KEPERCAYAAN DAN KEMUDAHAN TERHADAP KEPUASAN KONSUMEN SHOPEE PAY LATER DI PEKANBARU - Sartika, Dewi; Mulyana, Sri (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
Technological developments is currently making the financial business and loan business from cash (cash) to Cashless, from Credit to Online credit (Shopee Paylater). In Indonesia, Shopee Paylater is an example of a company that currently dominates the fintech market in the paylater sector in Indonesia. This study aims to determine whether there is a significant influence on the variables of ease and trust on the variable of customer satisfaction at Shopee Paylater in Pekanbaru. The population in this study were customer who had used the Shopee Paylater feature with a sample size of 57 respondents. The analysis used in this research is multiple linear regression method. The results showed that the Trust variable had an effect on customer satisfaction at Shopee Paylater. The ease variable has no effect on customer satisfaction at Shopee Paylater. Trust and ease variables. Influence on customer satisfaction at Shopee Paylater in Pekanbaru.